Spice Price Spikes: Simulating Impacts of Saffron Price Volatility in a Gendered Local Economy-Wide Model. (March 2017) - Filipski, Mateusz; Aboudrare, Abdellah; Lybbert, Travis J.; Taylor, J. Edward
Highlights: Connecting smallholder economies to world markets exposes them to market whims. LEWIE modeling can trace impacts of world price volatility on producer economies. Saffron harvesting requirements create highly seasonal, gendered labor markets. Female saffron workers are highly vulnerable to world price volatility. Summary: Access to international markets provides smallholders with unprecedented opportunities, but also exposes them to world market whims. We use a local economy-wide impact evaluation (LEWIE) model to analyze how the recent global saffron-price variability affected Morocco's Taliouine–Taznakht region, a specialized agro-export economy with a stark gender division of labor. Prices of saffron increased by 71% per year over the 2007–09 period before falling quickly back to their trend. Our modeling approach allows us to simulate such shocks and evaluate impacts not only on producers but also on the local economies around them. In our simulations, positive price-shocks and increases in productivity both cause large reallocations of labor resources, particularly for female workers at harvest time. We use Monte-Carlo simulations to evaluate how saffron-price variance affects the economy. Female wage income is especially sensitive to global price variability: a 100% increase in saffron-price variance leads to 133% increase in female wage income variance, but only 36% for males. Accounting for general-equilibrium effects is critical for understanding the ramifications of exposure to export price volatility in poor economies.